Global Trends in Natural Biopolymers in the 21st Century: A Scientometric Review - Sun, Yitao; Bai, Yinping; Yang, Wenlong; Bu, Kangmin; Tanveer, Sikander Khan; Hai, Jiangbo (Frontiers in Chemistry, 2022)
Since the 21st century, natural biopolymers have played an indispensable role in long-term global development strategies, and their research has shown a positive growth trend. However, these substantive scientific results are not conducive to our quick grasp of hotspots and insight into future directions and to understanding which local changes have occurred and which trend areas deserve more attention. Therefore, this study provides a new data-driven bibliometric analysis strategy and framework for mining the core content of massive bibliographic data, based on mathematical models VOS Viewer and CiteSpace software, aiming to understand the research prospects and opportunities of natural biopolymers. The United States is reported to be the most important contributor to research in this field, with numerous publications and active institutions; polymer science is the most popular subject category, but the further emphasis should be placed on interdisciplinary teamwork; mainstream research in this field is divided into five clusters of knowledge structures; since the explosion in the number of articles in 2018, researchers are mainly engaged in three fields: “medical field,” “biochemistry field,” and “food science fields.” Through an in-depth analysis of natural biopolymer research, this article provides a better understanding of trends emerging in the field over the past 22 years and can also serve as a reference for future research.